2023
DOI: 10.3390/bioengineering10040407
|View full text |Cite
|
Sign up to set email alerts
|

On Machine Learning in Clinical Interpretation of Retinal Diseases Using OCT Images

Abstract: Optical coherence tomography (OCT) is a noninvasive imaging technique that provides high-resolution cross-sectional retina images, enabling ophthalmologists to gather crucial information for diagnosing various retinal diseases. Despite its benefits, manual analysis of OCT images is time-consuming and heavily dependent on the personal experience of the analyst. This paper focuses on using machine learning to analyse OCT images in the clinical interpretation of retinal diseases. The complexity of understanding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The PR comprises rods and cones responsible for converting light into electrical signals that the brain can interpret. The NFL contains the axons of the ganglion cells, which transmit visual information from the retina to the brain [ 2 ]. The illustrative diagram of a healthy retina and OCT is given in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PR comprises rods and cones responsible for converting light into electrical signals that the brain can interpret. The NFL contains the axons of the ganglion cells, which transmit visual information from the retina to the brain [ 2 ]. The illustrative diagram of a healthy retina and OCT is given in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Another avenue for improvement involves incorporating multi-modal data for CNN training. Beyond OCT images, complementary information from diverse medical images, such as fundus photographs or fluorescein angiography images, enhances CNN performance and bolsters the model’s overall robustness [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retinal image diagnosis has shown an increased interest recently from various research groups. A large volume of research work has shown promising results in improving the accuracy and efficiency of OCT-based image analysis [4]. The accuracy of OCT image classification has shown considerable promise when using machine learning (ML) techniques.…”
Section: Introductionmentioning
confidence: 99%